Pendampingan Manajemen Ekstrakurikuler Kaligrafi di Lembaga Pendidikan Desa Kalisari Kecamatan Baureno Kabupaten Bojonegoro - Adawiyah, Robiatul; Rahmawati, Nur Laila; Syafaat, Rahmat Putra Ali Syafaat; Nafi, M. Bustanil Khoirun; Bakar, M. Abu; Cholis, M. Nur (Academia Publication, 2024)
Kalisari Village Baureno, has great potential for the development of calligraphy art, both in terms of human resources and student interest. Supporting the management of calligraphy-based extracurricular activities is essential in this context. Using the Asset-Based Community Development (ABCD) method, this approach focuses on empowering the existing assets in the village, The outcomes of this service are as follows: 1) The guidance on Calligraphy Extracurricular Management in Educational Institutions in Kalisari Village, consists of three main activities: Developing Calligraphy Extracurricular Management, Calligraphy Workshops, and Branding to enhance the image of the Educational Institution through calligraphy extracurricular branding, which can attract the local community and boost trust in the institution, 2) The impact of these changes aligns with the expected outputs, including improved student skills and creativity, more efficient extracurricular management, adaptation to technological and globalization changes, a structured extracurricular program plan, capacity building for teachers and mentors, and a system for monitoring and evaluating extracurricular activities, 3) Monitoring results show that the support for calligraphy extracurricular management has achieved 85.02%, significantly enhancing the development of calligraphy extracurricular management in educational institutions in Kalisari Village. Reflective results indicate that the most significant change experienced by most respondents is the increased involvement of stakeholders in managing extracurricular activities, particularly in calligraphy, leading to synergy among various assets for greater potential.